Analysis of 21st Century Entrepreneurship Skills from the Perspective of Entrepreneurial Education and Training - Rachmawaty Kadir; Andi Naila Quin Azisah Alisyahbana; Fajriani Azis (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This study aims to describe the implementation of entrepreneurship education and training at the Young Entrepereneur School South Sulawesi (YESS) and to find out whether entrepreneurship education and training at YESS in the South Sulawesi Cooperatives and SMEs Office is in accordance with the desired skills in the 21st century. The data collection techniques used in this study were interviews, observation and documentation. The data analysis method used was descriptive qualitative analysis with an interactive analysis model from Miles and Huberman. The results showed that the implementation of YESS is structured and programmed. Learning for 3 months each with teaching materials tailored to the important points of learning each month. The suitability of YESS with the desired skills in the 21st century can be said to be appropriate. With a learning concept of 20% theory and 80% practice, it is able to provide knowledge and provision of communication skills, work together, think critically and solutively as well as create and innovate to students. Although the effects of learning have not been able to be fully felt, this is an investment to be better and more competent in the future.